Fault-Based Liability Vs. Strict Liability: Comparative Study of the Concept of Unlawful Acts Indonesia – Japan - Wilhelmina Setia Atmadja; Gavra Datadavie Ginting; Maheswari Queena Dewani; Jason Marvin Wijaya; Rastra Judea Satyawada Pattiwael; Yudhiran R. V. M. Demonggreng (International Journal Labs, 2025)
This research analyzes the comparative concepts of fault-based liability and strict liability in torts under Indonesian and Japanese civil law. Although both jurisdictions adopt the European-Continental legal system, the approaches to liability reflect different historical, political, and social contexts. The research employs a normative (doctrinal) juridical approach, supported by secondary legal materials. Findings show that fault-based liability, as codified under Article 1365 of the Civil Code and Article 700 of the Civil Code of Japan, remains the general principle in determining liability, placing the burden of proof on plaintiffs. However, strict liability has emerged in special laws, particularly in consumer protection and environmental law. Landmark cases such as PT Newmont Minahasa Raya in Indonesia and the Minamata case in Japan illustrate the challenges and transitions between these two liability regimes. The study concludes that a balanced dual approach is necessary. Fault-based liability ensures legal certainty and fairness for defendants, while strict liability strengthens victim protection and deterrence. Ultimately, harmonizing both principles enhances access to justice, accommodates social needs, and aligns with global legal trends.